Ã¢â‚¬Å“BatikÃ¢â‚¬Â Industry Wastewater Treatment via Coagulation-Flocculation Process and Adsorption Using Teak Sawdust Based Activated Carbon - Handayani, Prima Astuti; Cholifah, Umi; Ulviana, Ria; Chafidz, Achmad (Jurnal Bahan Alam Terbarukan, 2019)
Untreated wastewater of Batik industry can pollute the environment because it contains metal compound, COD, BOD, which are higher than the allowable values. Therefore, a treatment of this wastewater prior discharging to water stream (i.e. river) is very important. This research aims to investigate the use of Teak sawdust as activated carbon, and also the effect of adsorbent concentration, adsorption contact time, as well as coagulation-flocculation-adsorption sequencing process to the level of COD, BOD, and Zn in Batik wastewater. The Batik wastewater used for this research obtained from Batik industry in Rembang, which mostly used naphtol as the coloring agent. The wastewater was initially treated by coagulation-flocculation process, followed by adsorption process. The coagulant-flocculant used in this research was 1 g/L of alum and 3 g/L of lime. Whereas, the adsorbent used was activated carbon made from Teak sawdust with variation of concentrations: 10, 16, 23, and 26 g/L. Whereas, the adsorption contact times were 20, 40, 100, 160, and 220 minutes. The results showed that the coagulation-flocculation process was able to decrease the levels of COD, BOD, and Zn by 73.28%, 73.62%, and 79.21% respectively. Additionally, the adsorption process by activated carbon also further decreased the levels of COD, BOD, and Zn significantly. Based on the results, the optimum concentration of activated that gave the best result was 26 g/L with 220 minutes contact time. Overall, the combination of coagulation-flocculation and adsorption sequencing process was able to decrease the level of COD, BOD, and Zn up to 96.69%, 96.90%, and 91.90% respectively.